Genome-wide identification and functional analysis of long non-coding RNAs in Chilo suppressalis reveal their potential roles in chlorantraniliprole resistance - Huang, Shuijin; Jing, Dong; Xu, Lu; Luo, Guanghua; Hu, Yanyue; Wu, Ting; Hu, Yao; Li, Fei; He, Kang; Qin, Wenjing; Sun, Yang; Liu, Hui (Frontiers in Physiology, 2023)
Long non-coding RNAs, referred to as lncRNAs, perform essential functions in some biological processes, including reproduction, metamorphosis, and other critical life functions. Yet, lncRNAs are poorly understood in pesticide resistance, and no reports to date have characterized which lncRNAs are associated with chlorantraniliprole resistance in Chilo suppressalis. Here, RNA-seq was performed on two strains of C. suppressalis exposed to chlorantraniliprole: one is a susceptible strain (S), and the other is a resistant strain (R). In total, 3,470 lncRNAs were identified from 40,573 merged transcripts in six libraries, including 1,879 lincRNAs, 245 intronic lncRNAs, 853 sense lncRNAs, and 493 antisense lncRNAs. Moreover, differential expression analysis revealed 297 and 335 lncRNAs upregulated in S and R strains, respectively. Differentially expressed (DE) lncRNAs are usually assumed to be involved in the chlorantraniliprole resistance in C. suppressalis. As potential targets, adjacent protein-coding genes (within <1000 kb range upstream or downstream of DE lncRNAs), especially detoxification enzyme genes (cytochrome P450s, carboxyl/cholinesterases/esterases, and ATP-binding cassette transporter), were analyzed. Furthermore, the strand-specific RT-PCR was conducted to confirm the transcript orientation of randomly selected 20 DE lincRNAs, and qRT-PCR was carried out to verify the expression status of 8 out of them. MSTRG.25315.3, MSTRG.25315.6, and MSTRG.7482.1 were upregulated in the R strain. Lastly, RNA interference and bioassay analyses indicated overexpressed lincRNA MSTRG.7482.1 was involved in chlorantraniliprole resistance. In conclusion, we represent, for the first time, the genome-wide identification of chlorantraniliprole-resistance-related lncRNAs in C. suppressalis. It elaborates the views underlying the mechanism conferring chlorantraniliprole resistance in lncRNAs.